DNA barcode characteristics of Paphiopedilum supardii Braem & Loeb - Mukhamad Su'udi; Vita Sindiya; Tri Ratnasari; Dhiyaul Kholis; Dwi Setyati; Husnatun Nihayah (Jurnal Ilmu Pertanian Indonesia, 2026)
Paphiopedilum is a protected orchid (Orchidaceae) genus with the most endangered species due to its unique aesthetic qualities, totaling 15 species. The excessive exploitation of orchids has led to a decline in their natural populations. This has prompted comprehensive conservation efforts to preserve these species. However, it is quite challenging to identify orchids that have not yet bloomed because of the similar morphology of their vegetation among closely related species, necessitating alternative identification approaches that are both rapid and accurate, especially for endangered orchids. DNA barcoding is a rapid and accurate molecular method for species identification. In this study, the selected rare orchid was Paphiopedilum supardii Braem & Loeb. The research procedure included DNA sample isolation using a NEXprepTM Plant DNA Mini Kit, DNA amplification using rbcL and ITS primers, PCR product purification, and sequencing. Based on the research results, DNA samples were amplified using rbcL and ITS primers. The DNA band resulting from rbcL primer amplification was 600 bp in size, whereas the ITS amplification result was 900 bp. The PCR products were then purified directly using a Purification Kit (Jena Bioscience). The PCR and purification results were separated on a 1.25% agarose gel. Based on data analysis, BLAST results from NCBI and sequence alignment using MEGA11, Clustal X2, and GeneDoc showed that the rbcL sequence had a higher homology level than ITS. Therefore, the ITS sequence is more specific for use as a molecular marker in DNA barcoding research on P. supardii. Keywords: ITS, Molecular identification, P. supardii, rbcL